Novel additive of PTFE@SiO2 core-shell nanoparticles with superior water lubricating properties. (October 2020) - Wang, Na; Wang, Honggang; Ren, Junfang; Gao, Gui; Chen, Shengsheng; Zhao, Gengrui; Yang, Yawen; Wang, Jinqing
Abstract: In order to solve the problems of poor dispersibility and wettability, as well as unsatisfactory wear resistance and load capacity of polytetrafluoroethylene (PTFE) as water lubricating additive, a new type of PTFE@silica (PTFE@SiO2 ) core-shell nanoparticles was prepared by encapsulating SiO2 layer on the surface of PTFE via chemical bonding. Electron microscope analysis showed that the synthesized particles had well-defined core-shell morphology. Special double/multi-core structure and a reduced thickness of the intermediate shell were found, and the formation mechanisms were also explored in detail. The water contact angle measurement proved that the wettability of PTFE could be greatly enhanced by coating SiO2 layer. The friction tests were performed to investigate the water lubrication properties of PTFE@SiO2 additive, the results indicated that the core-shell PTFE@SiO2 nanoparticles possessed the superior tribological properties, and the maximum friction coefficient and wear volume were respectively decreased by 75% and 99% when compared with pure water and water with PTFE/SiO2 . Based on the analysis of worn surface, it was believed that the existence of core-shell structure and the formation of robust transfer film were the key to its excellent performance, and a possible lubrication mechanism was also proposed. Graphical abstract: Unlabelled Image Highlights: A novel PTFE@SiO2 core-shell nanoparticles with PTFE as the core and silica as the shell is synthesized. A special double/multi-core structure and a reduced thickness of the intermediate shell are found. PTFE@SiO2 exhibits excellent friction reduction and wear resistance properties as water lubrication additives. The existence of transfer film and core-shell structure ensures the superior tribological properties.